Experience Analysis and Sample Distribution Problems in Local Level Landscape Monitoring (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
After summarizing experience of various countries in the field of landscape monitoring, it appears that the real changes of landscape have to be observed in a large scale (not smaller than 1:10,000) in order to avoid generalization of small landscape elements. Usually there are several levels of distributing the places of monitoring: 1) the level of sample area, when monitor territories are stratified by landscape types; 2) the level of investigation site that is distinguished inside the sample area for the more detailed research; 3) the level of transect or field investigation site, sometimes created in order to multiply the statistical data for some special aspect of monitoring. The paper offers an original method of distributing the landscape sample areas in Lithuanian territory, differing from most methods based on random choose of sample areas though thorough analysis of the analogous methods abroad was performed.